(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
In the past, the spread of a pandemic has often overlapped and exacerbated its impact on the socio-economic conditions of the affected populations. When a significant contraction in economic activities occurred to contrast the epidemic, the result was a worsening of the gaps among social classes and an expansion of existing inequalities. Based on these assumptions, the article presents the effects that the COVID-19 pandemic has had on Namibia. Through the review of the existing literature and secondary sources, the relationship between the COVID-19 infection and the socio-economic conditions in the country was analyzed, concluding that, in order to have long-term effects and not to harm the more marginalized social classes, the measures put in place by the government should have been holistic, and aimed at combating both the biological factors of the pandemic and existing inequalities.